2018
DOI: 10.1039/c8bm00478a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced healing activity of burn wound infection by a dextran-HA hydrogel enriched with sanguinarine

Abstract: Burn wounds are associated with a series of risks, such as infection and pathologic scar tissue formation, which significantly delay wound healing and lead to complications. In this study, we successfully fabricated a dextran-hyaluronic acid (Dex-HA) hydrogel enriched with sanguinarine (SA) incorporated into gelatin microspheres (GMs), which had high porosity, good swelling ratio, enhanced NIH-3T3 fibroblast cell proliferation, and sustained SA release profile. The in vitro degradation results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…8,9 With better understanding of the wound repair and management process, numerous biomaterials have been created to mimic the natural environment for skin regeneration, and accelerate cell proliferation and induce extracellular matrix (ECM) reproduction. 10,11 To date, a number of naturally derived polymers, including polysaccharides and proteins have been widely utilized in the eld of tissue engineering scaffolds, due to their excellent hydrophilicity, biodegradability and biocompatibility. [12][13][14] In particular, sodium alginate, a seaweed-derived polysaccharides, is preferred for its gelling property, excellent biocompatibility, and source-abundance.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 With better understanding of the wound repair and management process, numerous biomaterials have been created to mimic the natural environment for skin regeneration, and accelerate cell proliferation and induce extracellular matrix (ECM) reproduction. 10,11 To date, a number of naturally derived polymers, including polysaccharides and proteins have been widely utilized in the eld of tissue engineering scaffolds, due to their excellent hydrophilicity, biodegradability and biocompatibility. [12][13][14] In particular, sodium alginate, a seaweed-derived polysaccharides, is preferred for its gelling property, excellent biocompatibility, and source-abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the in vitro antimicrobial action of the formulation was evaluated against MRSA and E. coli, along with the mechanical properties and drug release pattern. In summary, the in vitro assay demonstrated that the hydrogel promoted a sustainable release of sanguinarine and preserved its antimicrobial activity [73].…”
Section: Hyaluronic Acid-based Formulationsmentioning
confidence: 87%
“…The obtained results showed that SA/GMs/Dex-HA hydrogel favored the healing process of burn lesion infected by MRSA when compared with rat treated with dextran-hyaluronic acid hydrogel or dextran-hyaluronic acid hydrogel incorporated with sanguinarine. In fact, the mice treated by SA/GMs/Dex-HA showed better profiles of re-epithelialization and extracellular matrix remodeling [73]. Furthermore, the treatment down-regulated the amounts of TGF-β1 (transforming growth factor-β1; related with hypertrophic scars and keloids formation due to myofibroblast differentiation [109,110]) and TNF-α; and up-regulated the expression of TGF-β3 (transforming growth factor-β3; inductor of collagen synthesis and fibroblast proliferation [111]).…”
Section: Hyaluronic Acid-based Formulationsmentioning
confidence: 93%
See 1 more Smart Citation
“…When the hydrogels were submerged in PBS in the presence of hyaluronidase, the weight loss by degradation was significantly higher than that in PBS solution ( Figure 3B). All of the hydrogels degraded by 82-93% after 28 days; this fast degradation rate was related to the β-elimination caused by hyaluronidase (Zhu et al, 2018b). Compared with OHA/HA-ADH, the OHA/HA-ADH/O-HACC and OHA/HA-ADH/N-HACC hydrogels shown a lower weight loss ratio.…”
Section: Physical and Mechanical Properties Of Hydrogelsmentioning
confidence: 93%